Pengurusan seni arca Raja Shahriman di galeri Pelita Hati, Bangsar, Kuala Lumpur - Raja Junaidah, bt Raja Daud@R. Hussin. (Universiti Malaysia Sarawak (UNIMAS), 2013)
This researched is to identify, examine and analyze the management methods conducted by Galeri Pelita Hati, at Bangsar for sculpture produced by Raja Shahriman. The objective of this researched to determine the types and techniques of sculpture, examine the management Raja Shahriman works, and also analyze the themes and images that often made an issue that Raja Shahriman to do. This researched uses the Classical Henri Fayol Management Theory popularized by Gerald Cole in the book Management Theory and Practice. This researched was carried out through qualitative methods of interviews with the gallery and sculptor Raja Shahriman and make observation about the process of making sculpture. The findings of this researched is management theory that forms on Henri Fayol's has relation between researchers, artists, enthusiasts and management as a compilation of all the parties involved thought unite in the form of sculpture works.